Diversified Treatment Options of Adult Stem Cells for Optic Neuropathies. (September 2022) - Tan, Shaoying; Yao, Yao; Yang, Qichen; Yuan, Xiang-Ling; Cen, Ling-Ping; Ng, Tsz Kin
Optic neuropathies refer to a group of ocular disorders with abnormalities or dysfunction of the optic nerve, sharing a common pathophysiology of retinal ganglion cell (RGC) death and axonal loss. RGCs, as the retinal neurons in the central nervous system, show limited capacity in regeneration or recovery upon diseases or after injuries. Critically, there is still no effective clinical treatment to cure most types of optic neuropathies. Recently, stem cell therapy was proposed as a potential treatment strategy for optic neuropathies. Adult stem cells, including mesenchymal stem cells and hematopoietic stem cells, have been applied in clinical trials based on their neuroprotective properties. In this article, the applications of adult stem cells on different types of optic neuropathies and the related mechanisms will be reviewed. Research updates on the strategies to enhance the neuroprotective effects of human adult stem cells will be summarized. This review article aims to enlighten the research scientists on the diversified functions of adult stem cells and consideration of adult stem cells as a potential treatment for optic neuropathies in future clinical practices.